ANALYSIS OF KNOWLEDGE MANAGEMENT IN IMPLEMENTING HUMAN RESOURCE POLICY AT UNIVERSITY OF CANTERBURY, NEW ZEALAND - Tenglewier, Michael Morljaya; Saerang, David Paul Elia; Mekel, Peggy Adeline (Universitas Sam Ratulangi, 2014)
Nowadays, in the complex and rapidly changing environment, innovation plays a critical role in enabling a firm to obtain a sustainable competitive advantage. While it is often happen that the desired competitive strategy/Human Resource Policy(which is planned in the corporate level of organization) is not met with the actual Human Resource practice at the operational level of organization. This problem can leads to the failure in achieving the intended organizational performance/a sustainable competitive advantage. The research objective is to analyze the role of knowledge management activities in affecting the implementation of human resource policy to become the desired human resource practice. This research uses qualitative approach and descriptive method. The population of this research is the management of University of Canterbury and the sample is an interview with Mr. Paul O’Flaherty as University of Canterbury’s Human Resource Director. The result shows that the knowledge management activities, such as employee participation, play a critical role in enabling the University of Canterbury to obtain their desired competitive strategy/desired human resource practice. Keywords: knowledge management, human resource policy